2012
DOI: 10.1111/j.1749-6632.2012.06520.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular targets in heart failure gene therapy: current controversies and translational perspectives

Abstract: Gene therapy of heart failure is gaining momentum as a result of the recent successful completion of phase II of the CUPID trial, which showed clinical safety and efficacy of an adeno-associated viral vector expressing SERCA2a. Resorting to gene therapy allows the manipulation of molecular targets not presently amenable to pharmacologic modulation. This review focuses on the molecular targets of heart failure gene therapy that have demonstrated translational potential. At present, most of these targets are rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 62 publications
0
45
0
Order By: Relevance
“…107 Dysregulation of Ca 2+ cycling and reduction of SERCA2a activity represent hallmarks of heart failure and are recognized as major pathogenic drivers in diseased hearts. As reviewed extensively elsewhere, 6,107 Hajjar et al revealed that the levels of SUMO1 (but not SUMO2/3) are decreased in a murine heart failure model and that SERCA2a is critically and positively regulated by SUMO1 conjugation. 47 Identification and mutation of the 2 major SUMOylation sites in SERCA2a (K480R and K585R) revealed that loss of SUMOylation significantly decreases ATP-binding affinity and ATPase activity of SERCA2a, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…107 Dysregulation of Ca 2+ cycling and reduction of SERCA2a activity represent hallmarks of heart failure and are recognized as major pathogenic drivers in diseased hearts. As reviewed extensively elsewhere, 6,107 Hajjar et al revealed that the levels of SUMO1 (but not SUMO2/3) are decreased in a murine heart failure model and that SERCA2a is critically and positively regulated by SUMO1 conjugation. 47 Identification and mutation of the 2 major SUMOylation sites in SERCA2a (K480R and K585R) revealed that loss of SUMOylation significantly decreases ATP-binding affinity and ATPase activity of SERCA2a, respectively.…”
mentioning
confidence: 99%
“…Researchers have characterized changes in gene activity and posttranslational modifications (PTMs) of specific cardiac proteins, contributing to impaired cardiac contractility and promoting pathological mitochondrial or metabolic alterations. 6,7 However, very few new drugs have emerged from such efforts, despite a rising number of patients suffering from heart failure. It seems likely that the prevalence of heart insufficiency will further increase in the future because of an aging population and a prolonged lifespan of cardiac patients, which represents a pressing need to develop new therapeutic approaches.…”
mentioning
confidence: 99%
“…They were used in craniofacial regeneration [4,25] and in reprogramming differentiated pancreatic exocrine cells in adult mice into cells that closely resemble β-cell structure and function [25]. Many other huge successes were achieved in several diseases such as corneal [7,26], retinal [27,28], cochlear [29], osteoarthritis [2,30], heart failure [31], and Parkinson's disease [32].…”
Section: Major Developments and Frontiers In Gene Therapymentioning
confidence: 99%
“…The functional remodelling is associated with alterations in the mRNA and protein expression and post-translational modification of a number of proteins involved in Ca 2+ signalling underlying excitation–contraction coupling 4. The extracellular matrix participates in the remodelling through the key process of myocardial fibrosis, which has also emerged as a therapeutic target in HF 9.…”
Section: Introductionmentioning
confidence: 99%